Demands, resources, meaningful work, and burnout of counselors‐in‐training. (28th April 2022) - Um, Byeolbee; Bardhoshi, Gerta
Abstract: This study examined the relationship between demands, resources, meaningful work, and burnout of counselors‐in‐training. The results of structural equation modeling indicated that demands and resources significantly predicted burnout of counselors‐in‐training, whereas meaningful work did not mediate the relationship between resources and burnout. Implications for counselor education are discussed.